Designing Solutions for the Retirement System – In Search of Balance between Economy and Health - Romaniuk, Piotr; Brukało, Katarzyna (Frontiers in Public Health, 2016)
Social security system currently face a number of difficulties arising of changes in the demographic structure of societies, like the decrease in fertility, lengthening of life expectancy and unfavorable change in the proportion of the population receiving retirement benefits to the population in working age. In result social security systems are being subjects to transition aimed ad securing their financial stability, part of which is a tendency to rise the retirement age and eliminate all the incentives to prematurely exit the labor market. On the other hand, this process of transition, as observed in Poland, is being driven mainly by political processes and due to economic reasons, while lacking public health evidence. This rises a danger that in final result the financial savings will be illusory only, and that the final configuration of the system will be inconsistent with the actual social needs of the population and will not efficiently protect against the social risks. In the article we present arguments for using the Healthy Life Years indicator in analyzes relating to the performance of social security systems, so that its construction will reflect differences in health status of different professional groups and system’s solutions in terms of both risk protection and prevention might be adjusted to conditions characterizing these groups.